SISTEM INFORMASI MONITORING HASIL AKTIVITAS TRIDHARMA DOSEN PADA STMIK KRISTEN NEUMANN INDONESIA MEDAN BERBASIS WEB - Zekson Arizona Matondang; Lukas Tarigan (UPPM, 2019)
Tridharma Higher Education consisting of Education and Teaching, Research and Development, andCommunity Service is the main task of Higher Education in Indonesia in organizing National Education.To achieve these three goals, it is necessary to support the existence of an integrated information systemthat can be used to evaluate and monitor independently (self assessment report), continuous and tieredof the three tasks of the Higher Education Tridharma.STMIK Kristen Neumann Indonesia already hasa computerized system in monitoring research, education and community service activities of lecturers,but no one has overseen or monitored routinely, resulting in difficulties when searching for lecturerdata that conducts research, education and community service activities, plus the number of lecturerswho forget the password (password) to log in a number of lecturers so that they are neglected in theinput and upload the lecturer tridarma file.